MAPPING AND IMPLEMENTING COMPLEXITY-BASED STRATEGIES IN ISLAMIC EDUCATION MANAGEMENT TO OPTIMIZE THE DYNAMIC INTERACTION BETWEEN TEACHERS AND STUDENTS IN THE LEARNING PROCESS - Muhammad Ihsan Dacholfany (International Journal of Teaching and Learning, 2023)
This research, titled "Mapping and Implementing Complexity-Based Strategies in Islamic Education Management to Optimize the Dynamic Interaction between Teachers and Students in the Learning Process," examined the intricate landscape of Islamic education to enhance the dynamic interplay between educators and learners. The study employed a mixed-methods approach, combining qualitative and quantitative methodologies. The research investigated the perceived effectiveness of current management strategies among teachers and students. Findings indicated a disjunction between teacher (72% satisfied) and student (42% satisfied) perspectives, emphasizing the need for a more empathetic understanding of student expectations within the Islamic educational framework. Additionally, the study explored the impact of complexity-based strategies on teacher and student experiences. Teachers who underwent specific training reported a substantial improvement (84%) in navigating the complexities of Islamic education. Qualitative insights underscored the adaptability of these strategies to diverse learning styles, aligning with the holistic goals of Islamic education. Results also demonstrated a positive impact on students, with increased enthusiasm for learning (67%) and a strengthened connection between academic and spiritual dimensions (72%). The study contributes to the existing literature by providing a unique lens for understanding the intricacies of educational management within the specific context of Islamic education. Acknowledging limitations in sample size and self-report data, the study suggests avenues for future research, including exploring the long-term sustainability of complexity-based strategies and their applicability in different cultural contexts. The findings of this research offer valuable insights for educators, administrators, and policymakers seeking to optimize the teacher-student dynamic in Islamic education.